Geochemistry and Petrography of the Strata Hosting the Flambeau Cu-Zn-Au Deposit : Revisiting Wisconsin's Only Past-Producing Volcanogenic Massive Sulfide Mine - Zens, Zacharie A.; Helmuth, Samuel L. (My University, 2015)
The purpose of this study was to revisit the Flambeau deposit and describe the geology, geochemistry, and petrography of the strata hosting the deposit.
Color poster with text, maps, images, and photographs.
Keywords: Sulfide mine; Volcanogenic massive sulfide (VMS); Flambeau; Geochemistry; Posters